In search of « camerounité »: on the reappropriation of emigrant authors in the Cameroonian press - Schumann, Clara (Études littéraires africaines)

(untitled) (Association pour l'Étude des Littératures africaines (APELA), 2019)
This article examines the reception and self-positioning of fiction authors of Cameroonian descent in the press of their country of origin. It draws upon material from two daily newspapers and two culture magazines and covers a period of 20 years between 1996 and 2016. The analysis of the material is based on the method of qualitative content analysis (Mayring 1983, Kuckartz 2012). The article focuses on gendered aspects of the reporting on emigrant authors, on the negotiation of their affiliation with several nationnal spaces, as well as on the strategies that are employed to reappropriate them into Cameroonian literature.